The role of managers in risk management - Jedynak, Piotr; Bąk, Sylwia (Contemporary organisation and management. Challenges and trends, 2020)
Management staff now face not so much a choice, but the necessity to implement a new management function, which is risk management. The purpose of this text is to identify the role of a manager in contemporary enterprise risk management. To achieve the intended objective, the evolution of the development of managerial functions in the area of risk management is presented, a catalogue of competences necessary to perform such functions is also presented along with a review of currently offered professional trainings which authorize the performance of the functions of risk managers, risk management specialists, and risk officers.